2023
DOI: 10.1186/s12872-023-03190-2
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved simulation of blood flow through left anterior descending coronary artery: effect of varying extent of stenosis on hemodynamics

Abstract: Background and objectives Real-time blood flow variation is crucial for understanding the dynamic development of coronary atherosclerosis. The main objective of this study is to investigate the effect of varying extent of stenosis on the hemodynamic features in left anterior descending coronary artery. Methods Various Computational fluid dynamics (CFD) models were constructed with patient-specific CT image data, using actual fractional flow reserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
1
2
0
1
Order By: Relevance
“…Moreover, The high OSI values (Fig. 6 ) particularly after the stenosis section highlight areas prone to disturbed flow, align with findings in preceding investigations 14 , 45 47 , and underscore the substantial alteration in coronary artery blood flow direction relative to the mean flow in this specific region. Previous studies have also demonstrated elevated RRT in regions characterized by reduced WSS 45 , 46 , which indicates regions prone to atherosclerotic plaque calcification 48 .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, The high OSI values (Fig. 6 ) particularly after the stenosis section highlight areas prone to disturbed flow, align with findings in preceding investigations 14 , 45 47 , and underscore the substantial alteration in coronary artery blood flow direction relative to the mean flow in this specific region. Previous studies have also demonstrated elevated RRT in regions characterized by reduced WSS 45 , 46 , which indicates regions prone to atherosclerotic plaque calcification 48 .…”
Section: Discussionsupporting
confidence: 88%
“…This comparative analysis underscores the critical role of an appropriate outlet boundary condition as it is capable of predicting the pressure/flow relationships in the arteries with a reasonable degree of accuracy 32 . As highlighted in prior research, the maximum pressure drop occurs near severe stenosis regions, and there is an elevated velocity of flow within constrained segments 14 , 22 , 34 , 43 . These findings are consistently depicted in Fig.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Индекс колебаний касательных напряжений позволяет оценить характеристики потока крови внутри сосудов и представляет собой безразмерную величину, которая изменяется от 0 до 0.5 и отражает степень осцилляции потока крови в течение сердечного цикла [30]. Значение OSI = 0 соответствует однонаправленному потоку крови, тогда как значение OSI = 0.5 указывает на полностью осциллирующий поток [31], что может привести к эндотелиальной дисфункции [32]. Индекс колебаний касательных напряжений вычисляется по формуле…”
Section: гемодинамические параметрыunclassified